Gambaran Self Efficacy Guru Sekolah Dasar dalam Pembelajaran yang Memanfaatkan Teknologi - Chrysantha, Charlotte; Purwanti, Margaretha; Aisyah, Aireen Rhammy Kinara (Fakultas Psikologi Universitas Sanata Dharma, 2024)
Teachers are the pillars of education who are in direct contact with students, thus playing a crucial role in guiding and teaching them. To perform their duties well, teachers must have confidence in their abilities, also known as self-efficacy. In today's era, it is a requirement for teachers to integrate technology into their teaching, starting from the elementary education level. With the unique characteristics of elementary school students, teachers must be able to use technology appropriately in elementary education to prepare students for the future. This study aims to explore the self-efficacy of elementary school teachers in teaching with technology and the types of technology used. This research was conducted with a quantitative approach using descriptive methods. The sampling method used convenience sampling techniques and obtained 139 participants. The population of this study were elementary school teachers in grades 1-3 and were in the age range of 40-60 years. Data collection was carried out using teacher self-efficacy measuring instruments and processed with descriptive statistics. The test results of this measuring instrument show that this measuring instrument is valid and reliable. The research results show that teacher self-efficacy tends to be high. This means that in learning that utilizes technology, elementary school teachers can; (1) overcome the challenges faced; (2) managing learning effectively and efficiently; (3) designing learning methods according to student characteristics; (4) prepare students to face the future. The types of technology used by elementary school teachers are Google Classroom, Whatsapp, Webex, Power Points and Paint. Suggestions for further research are (1) considering the data collection techniques used (2) adding questions to participant data.